Phytosterols from tinospora cordifolia in vivo and in vitro study - POOJA CHATURVEDI; VIJENDRA K. SHARMA (International Journal of Pharma and Bio Sciences, 2017)
Phytosterols, which include plant sterols, are phytosteroids similar to cholesterol which occur in animals. Phytosterols have ability to inhibit the absorption of cholesterol from our diets and have some immunological activity. The most common phytosterols are β-sitosterol, campesterol, stigmasterol and brassicasterol. The aim of the study is to isolate and characterize phytosterols from Tinospora cordifolia. Thin layer chromatography of various extract of T.cordifolia indicated the presence of phytosterol and the isolated compound was characterized by HPLC, GC-MS and IR. HPLC peak of isolated stigmasterol at retention time 2.242 mins was observed. The quantitative data revealed that the concentration of sterols in seeds, stem, leaf and callus were 18±0.67mg/gdw, 5±0.05mg/gdw 15±0.55mg/gdw and 10±0.48mg/gdw.The results showed that the plant T.cordifolia contains various bioactive compounds which are phytopharmaceutically important.